My wobbly tooth must not ever never fall out - Child, Lauren (New York : Grosset & Dunlap, 2006)
Lola does not "ever never" want her wobbly tooth to fall out until she learns that the Tooth Fairy will give money for it.
"Text based on script written by Samantha Hill ; Illustrations from the TV animation produced by Tiger Aspect."--T.p. verso.
First published: Great Britain : Puffin Books, 2006.
2.7
K-3
Keywords: Brothers and sisters -- Fiction; Teeth -- Fiction; Tooth Fairy -- Fiction; Siblings -- Fiction; Teeth -- Fiction; Tooth Fairy -- Fiction; Radio and television novels